Implementation of Fun English to Improve English Vocabulary of Sukahati Elementary School Students Through Audiovisual Media in Food and Beverage Material - Puspa Purwaning Rahayu (El-Ma'wa: Journal of Arabic, Translation and Linguistic, 2025)
The program was implemented at SDN Sukahati. SDN Sukahati is a state-owned school and operates at the elementary school level. Based on initial observations made by the author to one of the teachers at SDN Sukahati, where English learning in elementary school has just begun to be taught again and again English learning in elementary school is only done using ordinary textbooks which seem monotonous. This certainly has an impact on student motivation in learning which is lacking. Therefore, we have an initiative to provide a solution to this problem, namely by providing English learning to students, by implementing the Fun English method to improve the English vocabulary of 5th grade SDN Sukahati students, especially in the Food and Beverage material. The stages of the activity implementation are filling out a pretest by students, then teaching or providing treatment with audiovisual media in the form of videos, PowerPoint and flashcards to improve students' vocabulary, especially in the Food and Beverage material. The purpose of this community service is to improve students' English vocabulary, especially in the Food and Beverage material, and to increase students' motivation to learn English. The data collection method for this activity involved creating pretest and posttest questions. The data analysis used the N-Gain test to determine the categories of student learning outcomes using the Fun English method to improve English vocabulary. The results of this activity showed an N-Gain value of 0.91. Based on the N-Gain value obtained, this activity is categorized as effective. Therefore, it can be concluded that this activity was able to improve students' English vocabulary. The target outputs were an increase in students' English vocabulary and increased motivation to learn English. Academic outcomes included a Memorandum of Agreement (MoA) with partners and a report. Implementation of this program was hampered by the sudden change in participants, resulting in a shortage of copies of the pretest and posttest sheets. The second problem lay with the technician, who lacked an HDMI cable for the projector, ultimately using an older laptop with poor performance, resulting in slow loading times for videos and PowerPoint presentations.